Analisis Keterlambatan Pembelian Barang (Purchasing) di Perusahaan Pabrik Pengolahan Kelapa Sawit (Studi Kasus di PT Unggul Widya Teknologi Lestari Sulawesi Barat) - Muhammad Sapruwan (JURNAL CITRA WIDYA EDUKASI, 2012)
Industrial oil palm plantations are ideal not only focus on the activities of oil palm plantation and processing fruit only, but must be able to have parts that function with optimum support. Supporting part has a role as budgeting, warehousing, purchasing, and others, should be managed and functioned with a maximum. One of the very big role and become an important part of the purchase. In the oil palm plantation industry purchases made for the procurement of all equipment and materials needed to run industry. Starting from raw materials such as seeds to support the smooth administration of goods such as stationery, all managed by the purchasing department.Research and Field Work Practice aims to analyze the case of Purchase At Factory oil palm plantation of PT. Unggul Widya Teknologi Lestari. The problem is often the case that the purchase of a mistake buying in quantity and quality of goods and delay. This problem also happened in PT. Unggul Widya Teknologi Lestari. Delays providers of goods needed by the company can inhibit the activities of production, so the authors suggest to improve the procurement system, namely by Memubat date Order Receipt to help control and avoid delays in procurement of goods, socialize Standard Operating Companies regarding compulsory purchase where known by the operational, use of facilities and purchase information technology (software) in the procurement process at the company's overall material.